2007
DOI: 10.1134/s1560354707010042
|View full text |Cite
|
Sign up to set email alerts
|

Euler configurations and quasi-polynomial systems

Abstract: In the Newtonian 3-body problem, for any choice of the three masses, there are exactly three Euler configurations (also known as the three Euler points). In Helmholtz' problem of 3 point vortices in the plane, there are at most three collinear relative equilibria. The "at most three" part is common to both statements, but the respective arguments for it are usually so different that one could think of a casual coincidence. By proving a statement on a quasi-polynomial system, we show that the "at most three" ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…In the planar three-body problem, the number of central configurations is five. This fact was proved by Moulton [17] for a > −1 and by Albouy [2] for a > −2. Hampton and Moeckel [10] recently showed that the number of central configurations in the Newtonian planar fourbody problem is finite.…”
Section: Lemma 4 Every Planar Solution Of Constant Configurational Mmentioning
confidence: 74%
See 3 more Smart Citations
“…In the planar three-body problem, the number of central configurations is five. This fact was proved by Moulton [17] for a > −1 and by Albouy [2] for a > −2. Hampton and Moeckel [10] recently showed that the number of central configurations in the Newtonian planar fourbody problem is finite.…”
Section: Lemma 4 Every Planar Solution Of Constant Configurational Mmentioning
confidence: 74%
“…The equations of motion in Fujiwara coordinates for constant configurational measure solutions are given by substituting equations (1), (2), and (3) into (15). We thus obtain…”
Section: Lemma 4 Every Planar Solution Of Constant Configurational Mmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following we describe the results obtained. Notice that the bifurcation point m f shows a bifurcation inside the set of convex spatial central configurations, while it is conjectured that in the planar 4-body problem there is no bifurcation inside the set of convex planar central configurations, see for instance Albouy and Fu (2007). …”
Section: Analytic Continuation Of the Central Configurationsmentioning
confidence: 99%